Research and Development of a Device for Reducing Temperature in Heat Stroke Patients - Sodasri, Kotsakorn (Royal Thai Air Force Medical Gazette, 2024)
Introduction: This study aimed to develop a heat stroke life-saving device that can be used effectively and reduce the danger and complications for patients with this condition. In patients with heat stroke, the body temperature should be decreased by 0.2 degrees Celsius/minute. As a result, a device was developed to lower the body temperature to that level. Methods: A group of 17 individuals were selected to perform activities that would generate heat within the body without posing any risk. They were treated with the device, which is a cooling blanket. Another 1 week later, the same 17 people were treated as a control group using a body wipe method. The data collection was a temperature recording before and after the intervention, which recorded the changes every 5 minutes. The data was analyzed using descriptive statistics and using the Chi-square test for categorical variables and the T-test for continuous independent variables. The ANOVA test was used to test the difference in temperature after the experiment in the experimental and control groups. Results: The average temperature levels before the intervention of the two groups were not significantly different, while the average temperature after the intervention of both groups was statistically significantly different. When the average temperature reduction of both the experimental and control groups was compared, it was found that the average temperature reduction in the experimental group was significantly greater than the control group (p < 0.001). When considering the number of study participants who were able to reduce the temperature ≥ 0.2 degrees Celsius/minute, it was found that in the experimental group, there were 15 out of 17 people (88.2%), while in the control group, there were 2 out of 17 people (11.8%), which was a statistically significant difference (p < 0.001). Conclusions: This study on the development of heat stroke temperature reduction devices found that they effectively reduced the body temperature of heat stroke patients by ≥ 0.2 degrees Celsius/minute, ensuring safety and prevent complications. As a result, these devices are valuable for military medical units and those involved in recruiting new soldiers.